Beispiel Nr: 03
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-2/0)\qquad Q(-8/0) \\\\ \\ \textbf{Rechnung:} \\ P(-2/0)\qquad Q(-8/0) \qquad a=0 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=0(x+2)(x+8)\\ y=0(x^2+x \cdot 2 +8\cdot x +2\cdot 8 )\\ y=0(x^2 +10 x+16) \\ y= 0 $